Formulation and Evaluation of Micellar Water Containing Green Tea Leaf Extract (Camellia sinensis L.) - Savitri Cantika; Tri Danang Kurniawan; Dwi Kurnia Putri; Dwi Dominica; Suci Rahmawati (BEST Journal (Biology Education, Sains and Technology), 2026)
The use of natural ingredients in the cosmetics sector is currently growing, this study aims to formulate micellar water products from green tea leaf extract (Camellia sinensis L.). Green tea leaves are known to contain various active compounds such as flavonoids, saponins, alkaloids, and tannins that have antioxidant, anti-inflammatory, and antimicrobial properties, so they have potential in the formulation of micellar water products. Micellar water products have two surfactant parts that act hydrophilic which attracts water and hydrophobic parts that attract oil, so they can clean the face without needing to be rinsed which is able to remove dirt particles on the face. The extraction method used is maceration with 96% ethanol solvent and in the formulation of extract concentration variations used include 0.6%, 0.75%, and 0.9% with PEG-7 Glyceryl Cocoate surfactant of 0.2%. Based on observations in the physical evaluation of the preparation, the results of the four formulas are liquid, odorless and have a distinctive tea odor, clear color, transparent light brown, reddish brown, and reddish dark brown. The preparation with an average pH value of 5.12 - 6.44 has met the requirements of SNI-4380-1996 for topical use, while the viscosity results have an average of 1.5-1.24 cPs. The results of the irritation test showed no irritation from the four formulas that have been made. The results of the hedonic test showed that F3 was preferred by panelists in terms of aroma and texture, while for color F2 was preferred by panelists.